2013
DOI: 10.4269/ajtmh.2012.11-0209
|View full text |Cite
|
Sign up to set email alerts
|

Antimalaria Action of Antiretroviral Drugs on Plasmodium berghei in Mice

Abstract: Abstract. Malaria parasitemia enhances replication of human immunodeficiency virus. Antiretroviral drugs that possess antiplasmodial activity may reverse such an effect. Activity of the antiretroviral drugs lamivudine (L), zidovudine (Z), nevirapine (N), and stavudine (S) against Plasmodium berghei inoculated into 70 adult albino mice was investigated. Eight groups of five animals each were treated with different drugs as either curative or prophylactic regimens. These regimens were also given to four groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Most importantly, understanding the effect of AR compounds and ART on Plasmodium infection is of great clinical relevance, particularly in regions of HIV/ Plasmodium co-endemicity. While most studies on this subject have concentrated on evaluating the impact of AR compounds on the blood stages of human- (Skinner-Adams et al, 2004 ; Andrews et al, 2006 ; Redmond et al, 2007 ; Lek-Uthai et al, 2008 ; Nsanzabana and Rosenthal, 2011 ) and rodent-infective (Andrews et al, 2006 ; Martins et al, 2006 ; Akinyede et al, 2013 ; Abiodun et al, 2015 ) malaria parasites (Hobbs et al, 2013b ), much less is known on their effect on the pre-erythrocytic stage of Plasmodium infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, understanding the effect of AR compounds and ART on Plasmodium infection is of great clinical relevance, particularly in regions of HIV/ Plasmodium co-endemicity. While most studies on this subject have concentrated on evaluating the impact of AR compounds on the blood stages of human- (Skinner-Adams et al, 2004 ; Andrews et al, 2006 ; Redmond et al, 2007 ; Lek-Uthai et al, 2008 ; Nsanzabana and Rosenthal, 2011 ) and rodent-infective (Andrews et al, 2006 ; Martins et al, 2006 ; Akinyede et al, 2013 ; Abiodun et al, 2015 ) malaria parasites (Hobbs et al, 2013b ), much less is known on their effect on the pre-erythrocytic stage of Plasmodium infection.…”
Section: Discussionmentioning
confidence: 99%
“…The field combinations recommended by the WHO, specifically efavirenz + AZT + lamivudine, efavirenz + tenofovir + emtricitabine, and nevirapine + tenofovir + emtricitabine [ 131 ], were additionally evaluated in an in vivo setting, resulting in a reduction of parasite liver load, which could be further enhanced by the replacement of efavirenz by etravirine [ 38 ]. All PIs that display activity against hepatic infection by Plasmodium parasites have also been tested in vitro and/or in vivo against the ensuing blood stage of infection of P. berghei , P. cynomolgi , P. knowlesi , P. vivax , and P. falciparum [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 39 , 40 , 43 ], with lopinavir appearing to display the strongest activity among this class of compounds. Besides impacting asexual blood stages, the PIs lopinavir, saquinavir, and ritonavir also inhibited gametocytogenesis of P. falciparum parasites [ 33 ].…”
Section: Targeting the Liver Stage Of Plasmodium mentioning
confidence: 99%
“…The assessment of the activity of the NNRTIs efavirenz, etravirine, and nevirapine against the blood stage of P. falciparum revealed that the latter is not effective [ 31 , 34 ]. Further analysis of nevirapine in the context of an in vivo P. berghei infection showed only a modest impact in the control of parasitaemia [ 43 ]. Once in the insect vector step of the parasite’s life cycle, the NNRTI etravirine displayed activity against all sporogonic stages, whereas efavirenz only impacted oocyst formation and nevirapine was inactive [ 132 ].…”
Section: Targeting the Liver Stage Of Plasmodium mentioning
confidence: 99%